Capacity building and organizational development of kindergarten and playgroups principals in Gresik District - Rejeki, Asri; Sholichah, Ima Fitri (Community Empowerment, 2021)
The purpose of this service is to increase the capacity and organizational development of Kindergartens and playgroups principals in Gresik Regency. The methods used are lectures, self-reports, and assignments. This activity was attended by 74 school principals from 45 Kindergartens and 39 playgroups. The materials given were the strategic functions and roles of leaders in organizational development, the introduction of leadership behavior that is oriented towards organizational development, the process of organizational development: theory and practice, the development of a hardiness personality to support the effectiveness of organizational development. The result of this workshop was that the principal increasingly understood his/her strategic role as a leader in school organizations.